Percutaneous closure of patent ductus arteriosus in premature infants: A French national survey: A Titanic movement in technology and technique— Beware the icebergs!. Issue 5 (20th January 2020) - Wilson, Neil
Key Points: First national multicenter report of interventional closure of patent ductus arteriosus in preterm infants. Results describe commendable technical and procedural success of 99% with year‐on‐year tendency for intervention in smaller patients. Reported complications (8.9%) and outcome (1‐year mortality 6.8%) are far superior to contemporary surgical intervention but indicate room for improvement.